2(5X+9)=3(4X+7)

Simple and best practice solution for 2(5X+9)=3(4X+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5X+9)=3(4X+7) equation:


Simplifying
2(5X + 9) = 3(4X + 7)

Reorder the terms:
2(9 + 5X) = 3(4X + 7)
(9 * 2 + 5X * 2) = 3(4X + 7)
(18 + 10X) = 3(4X + 7)

Reorder the terms:
18 + 10X = 3(7 + 4X)
18 + 10X = (7 * 3 + 4X * 3)
18 + 10X = (21 + 12X)

Solving
18 + 10X = 21 + 12X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-12X' to each side of the equation.
18 + 10X + -12X = 21 + 12X + -12X

Combine like terms: 10X + -12X = -2X
18 + -2X = 21 + 12X + -12X

Combine like terms: 12X + -12X = 0
18 + -2X = 21 + 0
18 + -2X = 21

Add '-18' to each side of the equation.
18 + -18 + -2X = 21 + -18

Combine like terms: 18 + -18 = 0
0 + -2X = 21 + -18
-2X = 21 + -18

Combine like terms: 21 + -18 = 3
-2X = 3

Divide each side by '-2'.
X = -1.5

Simplifying
X = -1.5

See similar equations:

| 2(3x^2+3)-(x^2-5x+7)= | | -7(2-6)=70 | | (6-x)=30 | | (4a-3)(a+4)=0 | | 1x-2y=-4 | | a-18=54 | | g+4.5=12 | | 2/3(8a-15)=7/9 | | 18-2(7-4)= | | -5=4+k | | (-2x+7)-(x+11)= | | 3x-7x+37=2x+31 | | 4x-5+2x+10+4x-5=180 | | (4+9)(-11)=121 | | -5=4k | | -3(c+2)+c=14 | | 1000=d-100 | | -5(1+7n)-n=-113 | | -8t+2t= | | 3/5*5/12= | | 9c+6=10c | | 2m+7-7=10+2m+18 | | -10=c-14 | | 11r-7s= | | 15(7c-5)=8c-3 | | 57=50x | | 38-3x=4x-18 | | Z-9=54.9 | | h=t^2+5t+6 | | 3x+8-12=2(2x-3)+x | | 1/2(3x2) | | 2/3x9/16 |

Equations solver categories